2019
DOI: 10.17755/esosder.417877
|View full text |Cite
|
Sign up to set email alerts
|

Öz Bi̇li̇nç Psi̇ko-Eği̇ti̇m Programinin Üni̇versi̇te Öğrenci̇leri̇ni̇n Öz Bi̇li̇nç Düzeyleri̇ne Etki̇si̇

Abstract: Bu araştırma, öz bilinç psiko-eğitim programının üniversite öğrencilerinin öz bilinç düzeylerine etkisini incelemek amacıyla yapılmıştır. Araştırmanın amacına uygun olarak 2x3'lük split-plot (deney-kontrol grubu x ön-test/son-test/izleme-testi) faktöriyel desen kullanılmış, seçkisiz olarak 10'ar kişilik deney ve kontrol grupları oluşturulmuştur. Deney grubundaki öğrencilere, araştırmacılar tarafından geliştirilen her biri 90 dakika süren 10 oturumluk öz bilinç psiko-eğitim programı uygulanmıştır. Kontrol grubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Although it is not directly related to social psychology theories, theoretic approach developed by Fenigstein et al (1975) is also inspected under some of the studies held in Turkey. Alkal et al (2019) performed an experimental study on improvement of self-consciousness dimensions, which was applied together with a psycho-training programme and indicated that the training programme supported private and public self-consciousness of the attendees. In the study of Çelik and Çetin (2014) about the impacts of self-consciousness on solution of interpersonal conflicts showed the impacts of internal self-awareness, style consciousness, appearance consciousness and social anxiety on constructive and positive solution of conflicts.…”
Section: Perceived Inconsistency Between An Attitude … and A Behaviormentioning
confidence: 99%
“…Although it is not directly related to social psychology theories, theoretic approach developed by Fenigstein et al (1975) is also inspected under some of the studies held in Turkey. Alkal et al (2019) performed an experimental study on improvement of self-consciousness dimensions, which was applied together with a psycho-training programme and indicated that the training programme supported private and public self-consciousness of the attendees. In the study of Çelik and Çetin (2014) about the impacts of self-consciousness on solution of interpersonal conflicts showed the impacts of internal self-awareness, style consciousness, appearance consciousness and social anxiety on constructive and positive solution of conflicts.…”
Section: Perceived Inconsistency Between An Attitude … and A Behaviormentioning
confidence: 99%
“…Yüksek öz bilince sahip olan kişilerin kendileri hakkında daha çok bilgiye hâkim oldukları görülmektedir. Fenigstein'e (1979) göre öz bilinç: Bireyin kendini başkalarının açısından gözlemleyebilmesini ve değerlendirebilmesini sağlayan sosyal nesne olarak ifade edilmiştir (Alkal, Akça ve Korkmaz, 2019). Kendi duygularının farkında olmayan kişiler sürekli olumsuzluklarla mücadele ederken kendi duygularının farkında olan kişiler yani öz bilinç sahibi kişiler ise olumsuzluklar karşısında kendilerini daha kolay bir şekilde toparlayabilmektedirler.…”
Section: Introductionunclassified